Electronic commerce and web technologies : first international conference, EC-Web 2000, London, UK, September 4-6, 2000 proceedings - Bauknecht, Kurt, 1936-; Madria, Sanjay Kumar; Pernul, Gunther, 1961- (Lecture notes in computer science, 2000)
This book constitutes the refereed proceedings of the First International Conference on Electronic Commerce and Web Technologies, EC-Web 2000, held in London, UK in September 2000. The 42 revised full papers presented together with one invited paper were carefully reviewed and selected from 120 submissions. The book is divided in topical sections on Web application design, intellectual property rights, security and fairness, distributed organizations, Web usage analysis, modeling of Web applications, electronic commerce markets, XML, Web mining, electronic navigation, integrity and performance, facilitating electronic commerce, and mobile electronic commerce.